Distraction osteogenesis of the midface. Two clinical cases report - Torres Manríquez, Coral (2021)
Surgical correction of major facial asymmetries is a challenge for the surgical team. In such cases, treatment results from conventional surgical techniques are limited, which requires using other therapeutic tools. Bone distraction is one of them, as it allows controlled stretching of the bone callus previously developed through osteotomies. Distraction osteogenesis allows making changes in large bone positioning, favoring bone growth as an action mechanism. This article aims to describe the surgical results of intraoral distraction osteogenesis of the midface used in two patients with severe facial asymmetries related to congenital malformations. Diagnosis, planning, technological tools, surgical techniques, and results obtained are explained.